FINANCIAL PERFORMANCE ANALYSIS OF INSURANCE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Susilawati, Endang; Mulyana, Asep; Waruwu, Fotuho; Rizki, Vini (Jurnal Manajemen Dan Akuntansi Medan, 2025)
By using the Early Warning System ratio, this study aims to determine the financial performance of insurance companies listed on the Indonesia Stock Exchange from 2019-2023. For this study, purposive sampling technique was used, and the data analysis used was descriptive analysis. In this study, the ratio used is the fund adequacy ratio, which consists of the level of adequacy of funds ratio, incurred loss ratio, liabilities to liquid assets, and retention ratio. The results of the study show that insurance companies have had good financial performance, although when viewed from the retention ratio itself, they have poor financial performance. Keywords: Analisys Financial Performance, Early Warning System.